Radiosynthesis of the 11C‐methyl derivative of LBQ657 for PET investigation of the neprilysin inhibitor sacubitril. (8th January 2020) - Teyssier, Valentin R.; Simard, José‐Mathieu; Dornan, Mark H.; Tournoux, François; DaSilva, Jean N.
Abstract : Neprilysin, also known as neutral endopeptidase, is a cell surface membrane metalo‐endopeptidase that cleaves various peptides. Altered neprilysin expression has been correlated with various cancers and cardiovascular diseases. In this work, we present the radiosynthesis of the novel O ‐ 11 C‐methylated derivative of LBQ657 (a potent neprilysin inhibitor). (2 R, 4 S )‐5‐(Biphenyl‐4‐yl)‐4‐[(3‐carboxypropionyl)amino]‐2‐methylpentanoic acid [ 11 C]methyl ester ([ 11 C]MeOLBQ) is an analog of sacubitril where the alkyl ester is a 11 C‐methyl instead of an ethyl. [ 11 C]MeOLBQ was produced in a one‐pot two‐step synthesis. The O ‐ 11 C‐methylation of the pentanoic acid part was done with [ 11 C]methyl triflate followed by the deprotection of the tert ‐butyl ester precursor in acidic conditions. [ 11 C]MeOLBQ ([ 11 C]7 ) was produced in 9.5 ± 2.5% RCY (25 ± 6% decay‐corrected from [ 11 C]CO2, n = 3) high molar activity 348 ± 100 GBq/μmol (9425 ± 2720 mCi/μmol) at EOS, in high chemical (>95%) and radiochemical (>99%) purities. The total synthesis time including HPLC purification and reformulation was 29 minutes. To our knowledge, this is the first PET‐labeled analog of the clinically used NEP inhibitor sacubitril. Abstract : [ 11 C]MeOLBQ was produced from [ 11 C]methyl triflate followed by the deprotection of the tertbutylester in acidic conditions.